Literature Review : Penggunaan Modul IPA Berbasis Etnosains untuk Meningkatkan Literasi Sains Pada Siswa SD - Abdul Muizz Abdul Muizz; Suryanti; Binar Kurnia Prahani (Elementary Teacher Education Program, Majalengka University, 2023)
The development of the 2013 curriculum into an independent curriculum is the right way to respond to globalization. Science is one of the main subjects at the elementary level, but in its implementation it can be done separately, namely science and social studies. In reality, science subjects are less desirable, students are not interested and consider science subjects difficult to learn. Thus, at least teachers offer alternative ways to improve students' abilities by emphasizing lessons related to everyday life or culture, namely with ethnoscience, which aims to attract students' interest in learning. This study aims to analyze the use of ethnoscience-based science modules to improve science literacy in elementary school students. The method used is in the form of literature review. By looking for references to at least six articles in journals that are analyzed in inclusion and exclusion so that they are referenced in accordance with the goals to be achieved, especially with the help of Harzing's Publish or Perrish application and VOSViewer based on Google schoolar. From the results of the data collection, 200 articles were filtered and re-selected to produce 4 articles which were the results of selection according to more in-depth inclusion and exclusion criteria including titles, abstracts and discussion content. Based on the results of the analysis, no research results were found related to the use of ethnoscience-based science modules that can improve science literacy in elementary school students, and the lack of discussion words on VOSViewer that appeared and was less related to the research discussion. Thus, it can be concluded that the use of the IPA module is less of a trend in 2018-2023. Meanwhile, in terms of the feasibility of ethnoscience-based science modules, there is nothing to prove that the mod is feasible for elementary school students, because there is no suitability of scientific articles found, so further research is still needed regarding validity, practicality, and effectiveness. Thus, based on the results of this study, it can be a good opportunity for new researchers to conduct research on the topic to be a reference for researchers and teachers.